The context of children in Yoruba popular culture (2019)
The Yoruba of Southwestern Nigeria describes children as the heritage of the society because children occupy a special place in societal survival and continuity. Children are esteemed and appreciated. Thus, the embedded culture propagates the essentiality of children, the need for proper socialisation and internalisation to make a responsible being (Omoluabi). Also, children are prioritised above material wealth, and the essentiality of child wellbeing and education is emphasised in aspects of popular culture such as oral poetry, proverbs, local songs and popular music among others. Using extant elements of Yoruba popular culture which have remained dominant, this article contextually examines the value of children among the Yoruba